2021
DOI: 10.1523/jneurosci.0653-21.2021
|View full text |Cite
|
Sign up to set email alerts
|

GCH1 Deficiency Activates Brain Innate Immune Response and Impairs Tyrosine Hydroxylase Homeostasis

Abstract: The Parkinson's disease (PD) risk gene GTP cyclohydrolase 1 (GCH1) catalyzes the ratelimiting step in tetrahydrobiopterin (BH4) synthesis, an essential cofactor in the synthesis of monoaminergic neurotransmitters. To investigate the mechanisms by which GCH1 deficiency may contribute to PD, we generated a loss of function zebrafish gch1 mutant (gch1 -/-), using CRISPR/Cas technology. gch1 -/zebrafish develop marked monoaminergic neurotransmitter deficiencies by 5 dpf, movement deficits by 8 dpf and lethality by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Specifically, GCH1 mediates the rate-limiting step for the production of tetrahydrobiopterin (BH4), an essential cofactor required for the synthesis of monoaminergic neurotransmitters such as serotonin and dopamine [ 59 ]. GCH1 deficiency was recently shown to activate the innate immune response in the brain [ 60 ]. Furthermore, genes involved in immunity and infection [e.g., chemokine ligand 19 (ccl19), dedicator of cytokinesis 8 (DOCK8), and intercellular adhesion molecule-1 (ICAM-1)] [ 61 , 62 ] were also significantly dysregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, GCH1 mediates the rate-limiting step for the production of tetrahydrobiopterin (BH4), an essential cofactor required for the synthesis of monoaminergic neurotransmitters such as serotonin and dopamine [ 59 ]. GCH1 deficiency was recently shown to activate the innate immune response in the brain [ 60 ]. Furthermore, genes involved in immunity and infection [e.g., chemokine ligand 19 (ccl19), dedicator of cytokinesis 8 (DOCK8), and intercellular adhesion molecule-1 (ICAM-1)] [ 61 , 62 ] were also significantly dysregulated.…”
Section: Discussionmentioning
confidence: 99%
“…All adult zebrafish were raised in standard conditions under project license PP5258250. The c9orf72 mutant line was generated using CRISPR/Cas9 as previously described 39,40 using standard Tracr RNA and a CrRNA targeting an mwo1 restriction enzyme site within exon 2 of the zebrafish c9orf72 (5’UAGAAGCUAAGCUCUGACUG), both purchased from Merck KGaA (Germany, Darmstadt). This complex was co-injected with Cas9 protein (M0386M, NEB, Ipswich USA) into the yolk of 1-cell stage WT zebrafish embryos.…”
Section: Methodsmentioning
confidence: 99%
“…The zebrafish has shown to be a promising complementary in vivo vertebrate model of neurodegeneration, demonstrating the key markers of pathology, including neuronal loss and gliosis, even during early larval stages, in models of various neurodegenerative conditions 22,[25][26][27][28][29][30][31][32] . Previous studies characterising c9orf72 deficient larval zebrafish utilised a knock down approach with Morpholinos 33 , and indicated that knockdown of c9orf72 in zebrafish resulted in axon outgrowth deficits in motor neurons and reduction in spontaneous movement 33 .…”
Section: Introductionmentioning
confidence: 99%
“…The GTP cyclohydrolase-1-tetrahydrobiopterin (GCH1-BH4) pathway is a lipid antioxidant pathway independent of the Xc-GSH-GPX4 axis and the NADPH-FSP1-CoQ10 pathway ( Liu M. et al, 2022 ). GTP cyclohydrolase-1 (GTP Cyclohydrolase-1, GCH1) is a rate-limiting enzyme of BH4 ( Larbalestier et al, 2022 ). overexpression of GCH1 enhances the production of BH4 ( Kraft et al, 2020 ), a potent free radical-trapping antioxidant that protects cells from Ferroptosis by reducing lipid peroxidation ( Vasquez-Vivar et al, 2022 ; Figure 2 ).…”
Section: The Basic Process Of Ferroptosis and Its Relation To Scimentioning
confidence: 99%